Using the Brazilian Immunization Information System: What is real? - Barroso Rodrigues, Samuel; Gonçalves Amaral, Gabriela; Santos Silva, Brener; Cunha Corrêa Freitas de Oliveira, Gabriela; Oliveira de Moraes Tavares, Laís; Conceição de Oliveira, Valéria; Albano de Azevedo Guimarães, Eliete (Revista Cuidarte, 2022)
Introduction: Public health information is essential for decision-making in the public policy context, therefore considered a basic tool for phenomenon interpretation. The objective of this study was to evaluate the use of the Immunization Information System by nursing professionals. Materials and Methods: An analytical cross-sectional study was conducted with nursing professionals in a municipality in the Western Macro-region of Minas Gerais State by means of a validated checklist. For analysis, a scoring system was used to rate their use of the information system as appropriate, partially appropriate, not appropriate and critical. The median was used as a summary measure for descriptive analysis and Pearson’s chi-square test was used to assess comparisons. Results: Out of 104 participating nurses, 14.4% reported having used records for vaccination information management; 93.3% performed vaccine inventory management, which was the only activity classified as appropriate; preparation of reports listing missed doses (39.4%), vaccination coverage (36.5%) and dissemination of consolidated reports (17.3%) were classified as critical. No statistically significant differences were found between the variables studied. Discussion: Underutilizing information systems has consequences for vaccination services, such as low vaccination coverage and variation in dropout rates, as well as hindering planning and decision making by vaccination center managers. Conclusions: Managing data in information systems should be recognized by healthcare professionals as a necessary, functional and applicable piece of the work process performed in vaccination centers.How to cite this article: Rodrigues, Samuel Barroso; Amaral, Gabriela Gonçalves; Silva, Brener Santos; Oliveira, Gabriela Cunha Corrêa Freitas de; Tavares, Laís Oliveira de Moraes; Oliveira, Valéria Conceição de; Guimarães, Eliete Albano de Azevedo.  Uso do Sistema de Informação de Imunização do Brasil: qual a realidade?. Revista Cuidarte. 2022;13(1):e2138. http://dx.doi.org/10.15649/cuidarte.2138
Keywords: Immunization Programs; Information Systems; Health Evaluation; Primary Health Care; Public Health Nursing